Implementation of Resource-Based Learning in Improving Critical Thinking Ability of Students of SMP N 1 Woja - Kamaluddin; Edi Firmansyah (JPSL : Jurnal Pendidikan, Sosial dan Lingkungan, 2025)
This study aims to describe the implementation of the Resource-Based Learning (RBL) model to develop critical thinking skills of SMP N 1 Woja students. Critical thinking is one of the 21st century skills that is very important in solving problems in the digital era and society 5.0. The RBL model allows students to access, assess, and synthesize learning resources to build knowledge independently. This research uses a qualitative approach with interview data collection methods and descriptive analysis. The results showed that the application of RBL was able to encourage students to think analytically, reflectively, and solutively through source exploration activities, group collaboration, and critical reflection. Supporting factors for the successful implementation of RBL are the availability of learning resources, students' digital literacy, technical support, and the teacher's role as a facilitator. Conversely, the inhibiting factors are limited access to sources, low levels of information literacy, time constraints, and teacher training. Thus, the use of RBL has great potential in developing critical, independent, and adaptive students, if supported by a conducive learning environment.